2019
DOI: 10.7224/1537-2073.2017-047
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Short Version of the Activities-specific Balance Confidence Scale in Multiple Sclerosis

Abstract: Background: Multiple sclerosis (MS) is a neurologic disease that results in balance and mobility impairments that are associated with elevated fall risk. One common patient-reported outcome measure of balance is the 16-item Activities-specific Balance Confidence (ABC) scale. The ABC scale is valid and reliable in assessing balance confidence in people with MS. However, a shorter, six-question version of the ABC scale, the ABC-6 scale, has been proposed to save time in a clinical setting. Thus, we assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The ABC-16 has the highest explanatory value, whereas performance-based tests could not adequately explain falls in those without clinical disability (10). Few studies were reported; however, ABC-6 also has good sensitivity in distinguishing fallers or participants with high risk fall in Parkinson's disease (71.4%) and pwMS (95%), and values are similar to the ABC-16 (12,29). Depression, fatigue, and cognitive processing speed assessed using SDMT were determinants of the ABC-16.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The ABC-16 has the highest explanatory value, whereas performance-based tests could not adequately explain falls in those without clinical disability (10). Few studies were reported; however, ABC-6 also has good sensitivity in distinguishing fallers or participants with high risk fall in Parkinson's disease (71.4%) and pwMS (95%), and values are similar to the ABC-16 (12,29). Depression, fatigue, and cognitive processing speed assessed using SDMT were determinants of the ABC-16.…”
Section: Discussionmentioning
confidence: 94%
“…Wood et al (12) reported moderate convergent validity and good internal consistency of the ABC-6 in pwMS. They also revealed that both the ABC-6 and ABC-16 had good sensitivity and specificity in distinguishing between pwMS with high fall risk and controls, whereas were less accurate at differentiating low and high fall risk of pwMS.…”
Section: Introductionmentioning
confidence: 99%
“…Steady-MS consists of 2 components: the first includes 25 questions targeting demographic information and MS symptoms ( Multimedia Appendix 1 ). These questions include age, sex, past history of falls, type of MS, history of MS, the 12-item Multiple Sclerosis Walking Scale (MSWS-12) [ 24 ], and the short form of the Activities Balance Confidence Scale (ABC-6; Figure 1 ) [ 25 ]. These questions were specifically chosen because they are associated with falls in people with MS [ 17 , 26 - 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…An Arabic version of the short, six-question version of the ABC scale was used (ABC-6), as it takes less time than the original 16-items ABC scale, it includes only six items out of the original 16-item scale which are the most balance-challenging tasks (1-standing on tiptoes reaching for something above your head, 2-standing on a chair reaching for something, 3-bumped into by people as you walk through the mall, 4-walking onto or off an escalator while holding onto a railing, 5-walking onto or off an escalator while holding onto parcels such that you cannot hold onto the railing, and 6-walking outside on an icy sidewalk) with less time-consuming to administer. 35 , 36 Patients were instructed to record their response for each item of the (ABC-6) scale. Higher scores of ABC indicating better balance confidence, and a score of <67% indicating a risk for falls.…”
Section: Methodsmentioning
confidence: 99%